Keadaan Sosial Ekonomi Dan Tingkat Kesejateraan Petani Padi Orang Asli Papua (OAP) Di Distrik Kurik Kabupaten Merauke - Astaurina, Endang; Widyantari, Ineke Nursih; Situmorang, Ferdinand C (MuJAgri: Musamus Journal of Agribusiness, 2024)
The objectives of the study are: (1) Knowing the socio-economic conditions of local rice farmers (OAP) in Kurik District, Merauke Regency. (2) determine the welfare level of local rice farmers (OAP) in Kurik District, Merauke Regency. This research will be conducted in December 2023-January 2024. The population in the study was 48 people. The sampling method uses the census method. The sample in this study was 48 people. The data used are primary data obtained through structured interviews. This research uses Descriptive Qualitative and Descriptive Quantitative data analysis techniques. The analysis methods used are Cost Analysis, Income Analysis and Farmer Exchange Rate Analysis. Social conditions of local rice farmers (OAP) in Kurik District, Merauke Regency; the age aspect of local rice farmers (OAP) is still on average productive age of 26-35 years old by 60%, the education aspect of local rice farmers (OAP) is on average at the high school education level of 30%, the aspect of the number of dependents of families of 1-3 people is as much as 83%; and the health aspect of local rice farmers (OAP) is 100% utilizing a healthy public center without hesitation in using health facilities to carry out treatment. The socio-economic conditions of local rice farmers (OAP), capital aspects, and costs that must be prepared by farmers consist of fixed costs and variable costs, with an average total cost of IDR 8.002.262 per production and an average total cost of IDR 11.885.436 per year. The income of local rice farmers (OAP) is quite low, with an average income of Rp 11.885.436 in one-time production and Rp 23.770.869 in annual income of local rice farmers (OAP) per year. The welfare level of local rice farmers (OAP) using farmer exchange rate analysis (NTP) was obtained at 0.75, meaning that if the farmer exchange rate (NTP) <1, then the local rice farmer family (OAP) has a welfare level that is not feasible to meet daily needs.